Caravan (Tufts Archival Research Center, 2007)
CARAVAN newsletter from October 19993. Includes articles on cigarette taxes and lists key figures in the fight. Discusses health care reform. Focuses on North Carolina legislators. Contains service awards and congratulates employee of the year. Names new CEO for Tobacco International.